Biocompatible ZrO2- reduced graphene oxide immobilized AChE biosensor for chlorpyrifos detection. (5th December 2016) - Mogha, Navin Kumar; Sahu, Vikrant; Sharma, Meenakshi; Sharma, Raj Kishore; Masram, Dhanraj T.
Abstract: Based on Acetylcholinestrase (AChE) inhibition, a novel biosensing electrode involving Reduced Graphene Oxide (RGO) supported Zirconium Oxide (ZrO2 /RGO) nanoparticles is fabricated for Chlorpyrifos (pesticide) detection. AChE/ZrO2 /RGO biosensor when used for pesticide detection, exhibited high sensitivity towards Chlorpyrifos. Typically AChE/ZrO2 /RGO biosensing electrode is capable of detecting Chlorpyrifos concentration as low as 10 − 13  M (with 28% enzyme inhibition). Furthermore the enzyme inhibition is remarkable high (> 70%) in case of high Chlorpyrifos concentration (up to 10 − 4  M). Our results indicate that AChE/ZrO2 /RGO is an efficient and biocompatible electrode that can be used for Chlorpyrifos detection in ultra low concentrations. Electrochemical sensing response of AChE/ZrO2 /RGO sensor revealed two different linear ranges of chlorpyrifos detection. The first linear response was observed from 10 − 13  M to 10 − 9  M whereas the second linear range was observed between 10 − 9  M to 10 − 4  M revealing complete saturation of enzyme active sites by Chlorpyrifos. Ameperometric response of AChE/ZrO2 /RGO electrode demonstrates constant decrease in the current with respect to increase in the Chlorpyrifos concentration. Graphical abstract: Highlights: RGO supported ZrO2 nanocomposite is investigate as AChE based biosensor. RGO/ZrO2 is an efficient matrix to detect pesticide in ultralow concentration. Proposed electrode in biocompatible, highly sensitive and cost effective. AChE/ZrO2 /RGO biosensor is portable and can be used at remote places.